Flexible and transparent graphene-based supercapacitors decorated with nanohybrid of tungsten oxide nanoflakes and nitrogen-doped-graphene quantum dots - Sial, Qadeer Akbar; Javed, Muhammad Sufyan; Lee, Young Jae; Duy, Le Thai; Seo, Hyungtak (Ceramics International, 2020)
Recently, the development of flexible and transparent (F-T) devices, including energy storage, is of interest for wearable electronics and emerging Internet of Things applications. However, it is challenging to secure the high-power density and high energy storing capacity of F-T energy-storing devices. Thus, our proposed strategy here is the combination of CVD graphene (as a charge collector) with a 2D-0D nanohybrid of tungsten oxide nanoflakes and nitrogen-doped graphene quantum dots (WO3 NFs and NGQDs, respectively, as active materials providing multiple bonding types) to produce high-performance F-T supercapacitor electrodes. Our wet-synthesis and spray-decoration of the WO3 NFs/NGQDs nanohybrid are economical and suitable for large-scale and patternable processes. The fabricated F-T electrodes own a high specific capacitance of 117 F/g (at a scan rate of 50 mV/s) and excellent capacitance retention of 98.91% after 5000 charging-discharging cycles. Our developed symmetric supercapacitor devices show a better specific capacitance of 178.82 F/g (at 50 mV/s scan rate), capacitance retention up to 95.29% after 5000 charging-discharging cycles, along with power and energy densities of 360.11 W/kg and 15.79 Wh/kg, respectively. Overall, the obtained results show the potential of our proposed strategy for creating superior F-T energy storage and the usability of our symmetric supercapacitors for practical applications.
Keywords: Capacitance retention; Charge collectors; High power density; High specific capacitances; Nitrogen doped graphene; Specific capacitance; Supercapacitor electrodes; Transparent graphene; Flexible; Graphene supercapacitor; Nitrogen-doped quantum dots; Transparent; Tungsten oxide